Lifestyles, choice of housing location and daily mobility. Conceptual framework, methods and preliminary results of the interdisciplinary research project "StadtLeben" - Joachim Scheiner; Birgit Kasper (European Regional Science Association (ERSA), 2002)
Today, spatial research and planning is confronted with complex frame conditions which have substantially changed in the past decades. Thus, a comprehensive social change is stated, giving new room for individual development, but on the other hand making new decisions necessary (cue: individualisation). At the same time, settlement structures and time-regimes - essential conditions for spatial mobility - have developed dynamically (cues: decentralisation, flexibilisation). These trends are spatially resulting: - in a growing demand for housing size, which is realised predominantly in suburban and post-suburban settlement forms, - in high volumes of traffic in leisure, holidays, supply and commuting which are realised primarily by car and - in leisure and holidays - also by plane, - in changing mobility rationales; for instance, migrations are increasingly substituted by high distance commuting, - in new, partially virtual mobility forms (internet surfing, e-commerce, online banking, 'virtual leisure', event leisure). These mobility forms are characterised by interdependencies with physical passenger travel and freight transport as well as locational choice. From the perspective of a sustainable urban development, these trends have to be partially assessed as incompatible. At the same time, they offer chances for a more sustainable configuration of locations and transport. For instance, the change from industrial to service society facilitates the renaissance of the spatial integration of housing and working. New information and communication technologies allow to reduce job and supply trips (tele working, e-commerce). However, hitherto research and planning show serious methodological problems in the consideration of the stated changes. The explanation patterns of existing approaches for spatial mobility are mainly based upon spatial and individual restrictions. Neither the increasing degrees of freedom nor the subjective rationales behind mobility decisions are adequately considered. The referee presents the conceptual framework, methods and preliminary results of the interdisciplinary research project "StadtLeben". In this project, transport researchers, urban planners, geographers and psychologists from the universities of Aachen, Dortmund, Berlin (FU) and Bochum are working together. The project is supported by the German Federal Ministry of Education and Research in the research programme "Building and Housing". The central research question focuses on the interrelation between social structures (lifestyles, milieus), space-time-structures, housing resp. choice of housing location, and everyday mobility. In exemplary study areas in the urban regions of Köln and Leipzig, the specific interdependency of lifestyles, milieus and space-time-structures (f.i. infrastructure facilities, characteristic urban structures) as central influences on spatial action is investigated. In doing so, it is assumed that these interdependencies are to be understood as "contextual figures" rather than as clearly defined one-directional causal chains. The proposed research approach shall help to investigate the complex and manifold interrelations between social and spatial structures as well as the choice of housing location and everyday mobility. By means of this advanced descriptive and explanatory approach, target group-oriented and efficient planning and design strategies shall be developed. Together with planning practitioners, action-oriented knowledge as well as suggestions for planning methods (participation, processes, competence) shall be derived.
Keywords: 330